Immunogenicity and Protective Activity of Pigeon Circovirus Recombinant Capsid Protein Virus-Like Particles (PiCV rCap-VLPs) in Pigeons (Columba livia) Experimentally Infected with PiCV - Huai-Ying Huang; Benji Brayan I. Silva; Shen-Pang Tsai; Ching-Yi Tsai; Yu-Chang Tyan; Tzu-Che Lin; Ronilo Jose D. Flores; Kuo-Pin Chuang (Vaccines, 2021)
Pigeon circovirus (PiCV) is the most recurrent virus diagnosed in pigeons and is among the major causative agents of young pigeon disease syndrome (YPDS). Due to the lack of an established laboratory protocol for PiCV cultivation, development of prophylaxis is hampered. Alternatively, virus-like particles (VLPs), which closely resemble native viruses but lack the viral genetic material, can be generated using a wide range of expression systems and are shown to have strong immunogenicity. Therefore, the use of VLPs provides a promising prospect for vaccine development. In this study, transfected human embryonic kidney (HEK-293) cells, a mammalian expression system, were used to express the PiCV capsid protein (Cap), which is a major component of PiCV and believed to contain antibody epitopes, to obtain self-assembled VLPs. The VLPs were observed to have a spherical morphology with diameters ranging from 12 to 26 nm. Subcutaneous immunization of pigeons with 100 µg PiCV rCap-VLPs supplemented with water-in-oil-in-water (W/O/W) adjuvant induced specific antibodies against PiCV. Observations of the cytokine expression and T-cell proliferation levels in spleen samples showed significantly higher T-cell proliferation and IFN- γ expression in pigeons immunized with VLPs compared to the controls (p < 0.05). Experimentally infected pigeons that were vaccinated with VLPs also showed no detectable viral titer. The results of the current study demonstrated the potential use of PiCV rCap-VLPs as an effective vaccine candidate against PiCV.